Quality Improvement in Atrial Fibrillation detection after ischaemic stroke (QUIT-AF). Issue 5 (2020) - Kishore, Amit K; Fletcher, Susan; Mason, Denise; Ashton, Christopher; Molloy, Jane; Fitchet, Alan
No abstract available